2021
DOI: 10.1111/codi.15771
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes after seton placement for perianal fistulas with and without Crohn’s disease

Abstract: Aim Perianal sepsis in Crohn's disease (CD) fistulas is managed with antibiotics and surgical drainage; a noncutting seton is used for an identified transsphincteric fistula tract. The optimal management following seton placement for initial control of perianal sepsis remains to be determined. Our main aim was to assess the success rates of curative surgery, seton removal or long‐term indwelling seton in patients with and without CD. Method This was a retrospective cohort of consecutive patients with a periana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…It has been found that CD patients with perianal fistula can considerably benefit from long-term management with seton. 15 As a result of our study, 94.4% of patients in the seton group experienced an improvement in their fistula; however, no significant difference was recorded between the two groups. According to Rosen et al investigation of 121 patients (80 men) suffering from intra-sphincteric fistula, 98% of patients achieved complete fistula resolving without fecal incontinence under cutting seton treatment.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…It has been found that CD patients with perianal fistula can considerably benefit from long-term management with seton. 15 As a result of our study, 94.4% of patients in the seton group experienced an improvement in their fistula; however, no significant difference was recorded between the two groups. According to Rosen et al investigation of 121 patients (80 men) suffering from intra-sphincteric fistula, 98% of patients achieved complete fistula resolving without fecal incontinence under cutting seton treatment.…”
Section: Discussionmentioning
confidence: 54%
“…To reduce fecal incontinence in perianal fistula cases, seton insertion can be used as a conventional therapeutic option to prepare the fistula for other procedures. It has been found that CD patients with perianal fistula can considerably benefit from long‐term management with seton 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery, the only curative treatment, obtained suboptimal results with high percentages of persistence or recurrence and a high risk of postoperative fecal incontinence [1,3]. The results are even worse in previously operated patients [1,3], and, in some cases, palliative treatment with long-term setons is considered [4,5].…”
Section: Introductionmentioning
confidence: 99%